Combinatorial interplay of RNA-binding proteins tunes levels of mitochondrial mRNA in trypanosomes - Dixit, Sameer; Lukeš, Julius (RNA, 2018)
MRP1/2 is a heteromeric protein complex that functions in the trypanosomatid mitochondrion as part of the RNA editing machinery, which facilitates multiple targeted insertions and deletions of uridines. MRP1/2 was shown to interact with MRB8170, which initiates RNA editing by marking pre-edited mRNAs, while TbRGG2 is required for its efficient progression on pan-edited mRNAs. Both MRP1/2 and TbRGG2 are capable of modulating RNA-RNA interactions in vitro. As determined by using iCLIP and RIP-qPCR, RNAs bound to MRP1/2 are characterized and compared with those associated with MRB8170 and TbRGG2. We provide evidence that MRP1 and MRB8170 have correlated binding and similar RNA crosslinking peak profiles over minimally and never-edited mRNAs. Our results suggest that MRP1 assists MRB8170 in RNA editing on minimally edited mRNAs.
Keywords: mitochondrie; RNA, Mitochondrial; protozoální proteiny; Protozoan Proteins; proteiny vázající RNA; vazba proteinů; RNA mitochondriální; Protein Binding; RNA Editing; RNA, Messenger; Trypanosoma; messenger RNA; RNA-Binding Proteins; editace RNA; Mitochondria